(untitled) (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2025)
The feasibility of next-generation urban power networks hinges on the ability of DC converters to replace their conventional counterpart. Reliability and efficiency are heavily contested points when discussing the challenges facing power electronics proliferation in power systems. Motivated to find a working solution, this paper presents the paradigm of the two-time scale converter. By employing a division in dynamics, interpreted from singular perturbation theory, a cost-effective redundancy can be attained in the form of complementary fast and slow subsystems. This enables the proposed converter to handle considerable perturbations with a quick response time and achieve cost-effective operation at steady state, thanks to the reduction in switching frequency. The overall controller scheme consists of an inner current control loop and an outer voltage control loop; the control laws are derived from a generic Lyapunov’s approach, which can be adapted to the characteristics of the voltage source. The simulation results demonstrated a seamless response to various types of perturbations and the proper handling of different omission fault scenarios.